(untitled) (Research, Society and Development, 2020)
The extraction of oil from various raw materials by enzymatic process has received great importance for being considered clean technology. In addition, the product obtained by enzymatic action has better yields as well as better chemical quality parameters, also better stability conditions. Thus, the objective of the present work was to optimize the murici pulp oil extraction process by enzymatic hydrolysis and to compare the thermo-oxidative stability of murici oil extracted by ultrasound-assisted enzymatic hydrolysis and the oil obtained by the classic method (Soxhlet). The results obtained showed a dependence on the dependent variable - yield (%) - as a function of the independent variables - enzyme concentration (%) and exposure time on ultrasound (min). From the applied statistical analysis, it was observed that the oil extracted by enzymatic hydrolysis showed greater thermal stability (400 °C) compared to that obtained by the classical method (384 °C). The analysis of oxidative stability showed greater propensity to oxidation the oil obtained by classical method compared to that obtained by enzymatic hydrolysis in 6 hours of induction at 110 °C. Thus, the oil obtained by enzymatic hydrolysis has properties superior to that obtained by the classical method and, thus, with better thermo-oxidative stability.